A British Expeditionary Force Armour. (October 2014) - Richardson, Thom
<x content-type="archive" xml:space="preserve">Abstract</x> The First World War saw a widespread reintroduction of helmets and body armour onto the battlefield. In England numerous companies made different forms of armour for private purchase. A particularly rare type, the British Expeditionary Force armour, is represented in the Royal Armouries by an example whose owner, a private soldier who survived the latter stages of the war, went on to an illustrious military career as a Lieutenant Colonel in the Royal Berkshire Regiment.